2014
DOI: 10.1016/j.scitotenv.2014.04.029
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for sensitivity of dune wetlands to groundwater nutrients

Abstract: . 2014. Evidence for sensitivity of dune wetlands to groundwater nutrients. Contact CEH NORA team at noraceh@ceh.ac.ukThe NERC and CEH trademarks and logos ('the Trademarks') are registered trademarks of NERC in the UK and other countries, and may not be used without the prior written consent of the Trademark owner.Manuscript for Science of the total environment ACCEPTED Dune slacks are seasonal wetlands, high in biodiversity, which experience considerable within-year and 24 between-year variations in water-ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 32 publications
(13 reference statements)
2
26
0
Order By: Relevance
“…By contrast, nitrate concentrations in Stream A, which drains the pastureland and flows onto the sand dune site, are significantly higher than those in stream B and previous studies have shown they can exceed the 50 mg/L threshold for designation of a nitrate vulnerable zone by the UK Environment Agency (Rhymes et al, 2014, Environment Agency, 2012. This implies that stream A has additional N inputs compared to stream B, these are likely to be from fertilisers leaching from the steep sloped pastureland adjoining the stream.…”
Section: Streamsmentioning
confidence: 84%
See 4 more Smart Citations
“…By contrast, nitrate concentrations in Stream A, which drains the pastureland and flows onto the sand dune site, are significantly higher than those in stream B and previous studies have shown they can exceed the 50 mg/L threshold for designation of a nitrate vulnerable zone by the UK Environment Agency (Rhymes et al, 2014, Environment Agency, 2012. This implies that stream A has additional N inputs compared to stream B, these are likely to be from fertilisers leaching from the steep sloped pastureland adjoining the stream.…”
Section: Streamsmentioning
confidence: 84%
“…Annual long term average rainfall at the site is 847mm .There are a number of potential pathways by which nutrients and coliforms can enter the site, these include streams and ditches, surface runoff draining agricultural land and flowing onto the site, seepage of nutrients into the groundwater flowing under the site, and on-site sources such as grazing cattle and rabbits. Previous work has previously shown a nitrogen groundwater contamination gradient that extends into the site from the fertilised pastureland on the south east border with groundwater travelling in a south westerly direction (Fig 1) (Rhymes et al, 2014). To determine the nature and pathways of the contamination, measurements were made bimonthly for a 12 month period (i.e.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations